The effect of physiotherapy and nutrition on pulmonary function tests, exercise capacity and quality of life in patients with chronic obstructive lung disease - Umut, Sema; Börekçi, Şermin; Demir, Tunçalp; Atam Taşdemir, Zeynep (Cerrahpaşa Medical Journal, 2019)
Objectives: The purpose of the study was to evaluate the relationship between body mass index (BMI) and pulmonary function tests, exercise capasity and quality of life in patients with COPD and to investigate the effect of physiotherapy and nutrition on pulmonary function tests, exerecise capacity and quality of life. Methods: Thirty-six patients with COPD were included in the study. According to their application priority the patients were divided in to three groups. Demographic data, physical examination, pulmonary function tests, arterial blood gas measurements, lung volume, difusion capacity, pulmonary muscle function tests, six minute walking test and St. George Respiratory Questionnaire (SGRQ) were performed on the first day and after 6 months. Diet counseling was given to group one (group 1) whereas pulmonary rahabilitation was started in group two (group 2) without any change in their medical therapy. Group 3 patients were followed with no alteration in their therapy. Patients in the control group were followed without any change in their medical therapy. Physical examination and all the analysis were repeated after six months. Results: The BMI decreased as the stage of the disease increased. After 6 months significant increase in VC, MIP (%), PaO2 and 6 minutes walking distance was observed in the physiotheraphy group (p<0.05). At the end of 6 months, there was an insignificant decrease in FVC and FEV1 parameters in the nutrition and control groups whereas an insignificant increase was observed in the physiotherapy group. A significant decrease was found in RV and PaCO2 (p<0.05), and a significant progress in the symptom and activity scores of the SGRQ questionnare (p<0.05) in the phsiotherapy group. Conclusion: Diet regulation made an improvement in quality of life and exercise capacity in COPD patients. Application of a physiotherapy improves the symtoms, functional parameters, exercise capacity and quality of life in patients with COPD.